The Development of Jelly Roll Deformation in 18650 Lithium-Ion Batteries at Low State of Charge. Issue 12 (6th August 2020) - Willenberg, Lisa; Dechent, Philipp; Fuchs, Georg; Teuber, Moritz; Eckert, Marcel; Graff, Martin; Kürten, Niklas; Sauer, Dirk Uwe; Figgemeier, Egbert
Abstract : In this paper, the origin of the jelly roll deformation in 18650 lithium-ion batteries is examined in more detail by combining volume expansion measurements, accelerated lifetime testing, and CT imaging. Based on the presented research, a theory is developed to determine the cause of the jelly roll deformation at low states of charge (0%–20% SOC). The diameter of the cell is increasing during ageing, which reflects the increase of the internal pressure. Continuously growing cover layers of chemical degradation explain the latter. It is concluded that for releasing internal pressure, the jelly roll starts to deform. This deformation accelerates the ageing processes by electrically isolating active material from the current collector and the formation of fresh SEI. In addition, the CT images are used to determine the time of the deformation. Conclusively, it is shown that the jelly roll deformation is driven by cyclic ageing. Due to the correlation of the mean diameter change and the capacity curve, the deformation of the jelly roll and thus the sudden cell death can be predicted by measuring the mean diameter change of the battery.